Frequency of Neonatal Hyperbilirubinemia in Maternal Hyperglycemia - Humaira Ashraf, Afra Rehman, Mehreen Yousaf Rana, Shoaibunissa, Ameena Saba, Arzoo Rahim (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the occurrence of newborn hyperbilirubinemia among women who were diagnosed as maternal hyperglycemia. Subject and Method: The present cross-sectional study was conducted in the OBS and Gynecology department of PNS Shifa Karachi. The study was done over the time period of six months. All pregnant women who visit antenatal clinics at PNS Shifa Hospital with a gestational age of 24 and 32 weeks undergoing a 75 gm 2 h glucose tolerance test and fulfilling criteria of IFG, IGT, or GIGT were included. After delivery, a 2 ml blood sample was drawn from each newborn and sent to the hospital diagnostic laboratory to evaluate the neonatal bilirubin level and serum bilirubin >300µmol/L after 96 hrs was considered as neonatal hyperbilirubinemia. All of the data was obtained using a study proforma. For the analysis of the data, SPSS software version 20 was utilized. Results: A total of 157 hyperglycemic mothers were studied; their average age was 28.20±4.67years and gestational ag was 37.11±3.22 weeks. Out of all, most of the women 100(63.7%) were multiparous. Caesarean section was done in 98(62.4%) cases. New born Neonatal hyperbilirubinemia was noted in 10.2% of the cases. The frequency of the neonatal hyperbilirubinemia was higher in the age groups of 19–30 years and >30 years, while findings were non-significant statistically according to maternal age and gestational age (p = >0.05). Conclusion: The study’s findings showed that 10.2% of women with diabetes were found to have newborns with hyperbilirubinemia. It was proven to be statistically insignificant based on maternal age and gestational age. Keywords: Maternal, hyperglycemia, hyperbilirubinemia